Greek Primary School Teachers’ Narratives About Their Role Negotiation During the Covid-19 Pandemic - Menelaos Tzifopoulos (Center for Educational Policy Studies Journal)
No one can dispute the fact that the teaching profession seemed to be tested during the coronavirus pandemic. Teachers were called upon to perform a difficult and multifaced role, without help and support from the state. The issues that teachers had to respond to and solve are related to their autonomy, their digital literacy competences and their relationships/cooperation with students. The new working conditions terrified teachers, who had to manage their digital classroom through a violent readjustment. Under these circumstances, Greek primary school teachers’ narratives offer us their phenomenological perspective on how they coped with their teaching duties during this period of health and educational emergency. An initial attempt is made to empathetically approach the ‘world’ of four teachers, while the subsequent interpretive and critical analysis serves as a means to illuminate ‘hidden’ beliefs of their professional role, the reshaping of their identity, and their adaptation to the online teaching context. Through their narratives, the teachers reflect on the issue of the lack of support from the state. They also note that they found it difficult to manage their e-classes in such a short time. Finally, there is a need for more effective preparation of teachers in times of uncertainty and crisis.